2012
DOI: 10.1371/journal.pone.0043829
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Age on Brain Edema Formation, Secondary Brain Damage and Inflammatory Response after Brain Trauma in Mice

Abstract: After traumatic brain injury (TBI) elderly patients suffer from higher mortality rate and worse functional outcome compared to young patients. However, experimental TBI research is primarily performed in young animals. Aim of the present study was to clarify whether age affects functional outcome, neuroinflammation and secondary brain damage after brain trauma in mice. Young (2 months) and old (21 months) male C57Bl6N mice were anesthetized and subjected to a controlled cortical impact injury (CCI) on the righ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
93
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(97 citation statements)
references
References 78 publications
(107 reference statements)
3
93
1
Order By: Relevance
“…The brain tissue properties used in the young adult, mature adult, and old age FE models are listed in Table D1 (see online supplement). Timaru-Kast et al (2012) found an 8% brain volume reduction when brain atrophy was measured through imaging in young (2 months) and old age mice (21 months). Based on these results, the brain volume (including all soft tissue regions and the ventricles) of the old age brain FE model was established by scaling the young adult brain model geometry with a factor of 0.97 in the x, y, and z directions with respect to the brain center of gravity.…”
Section: Assigning Brain Propertiesrepresentative Of Mature Adult Andmentioning
confidence: 95%
“…The brain tissue properties used in the young adult, mature adult, and old age FE models are listed in Table D1 (see online supplement). Timaru-Kast et al (2012) found an 8% brain volume reduction when brain atrophy was measured through imaging in young (2 months) and old age mice (21 months). Based on these results, the brain volume (including all soft tissue regions and the ventricles) of the old age brain FE model was established by scaling the young adult brain model geometry with a factor of 0.97 in the x, y, and z directions with respect to the brain center of gravity.…”
Section: Assigning Brain Propertiesrepresentative Of Mature Adult Andmentioning
confidence: 95%
“…In addition, it has been reported to regulate expression of various cytokines, cell adhesion molecules, oxidative-stress related enzymes, cell surface receptors, and acute-phase proteins associated genes. Glutamate homeostasis is abnormally affected by TBI which in turn leads to prolonged neuronal depolarization, ionic imbalance, enhanced calcium influx, and ATP depletion [28]. Literatures also indicate that NF-κB play a key role in stimulation of the glial cell proliferation, cerebral edema, and inflammation by upregulating the expression of glial fibrillary acidic protein (GFAP) [29], aquaporin-4 (AQP4) [30], and TNF-α [14], which have been used as markers of TBI-induced astrocyte proliferation, inflammation and cerebral edema, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…68) Interestingly, in the secondary injury process these pro-inflammatory cytokines always overexpress and play a deleterious role in damaging tissue. 69) In this study we mainly focused on the outcome of anti-inflammation changed by the three secondary injury therapeutic methods. It is noteworthy that osthole did not affect the number of GFAP in the similar model as our previous studies (the diameter of the needle is 1.1 mm and the speed of the insertion is faster than 100 µm/s), which may be related to the size of the wound area and the degree of trauma.…”
Section: Discussionmentioning
confidence: 99%